For an Alternative Genealogy of American Identity - Grgas, Stipe (2003)
The presentation argued that the present conjecture demands a revisionary take on the discipline of American Studies, What has emerged is the predatory nature of capitalism which can be conceptualized, it was argued, through a rereading of the gothic novel.